Facial Expressions of Emotion: Are Angry Faces Detected More Efficiently? - Elaine Fox; Victoria Lester; Riccardo Russo; Robert J. Bowles; Alessio Pichler; Kevin Dutton (2000)
The rapid detection of facial expressions of anger or threat has obvious adaptive value. In this study, we examined the efficiency of facial processing by means of a visual search task. Participants searched displays of schematic faces and were required to determine whether the faces displayed were all the same or whether one was different. Four main results were found: (1) When displays contained the same faces, people were slower in detecting the absence of a discrepant face when the faces displayed angry (or sad/angry) rather than happy expressions. (2) When displays contained a discrepant face people were faster in detecting this when the discrepant face displayed an angry rather than a happy expression. (3) Neither of these patterns for same and different displays was apparent when face displays were inverted, or when just the mouth was presented in isolation. (4) The search slopes for angry targets were significantly lower than for happy targets. These results suggest that detection of angry facial expressions is fast and efficient, although does not "pop-out" in the traditional sense.